2020
DOI: 10.1186/s40163-020-00126-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-period-cohort effects in half a century of motor vehicle theft in the United States

Abstract: Adopting and refining O’Brien’s S-constraint approach, we estimate age-period-cohort effects for motor vehicle theft offences in the United States for over half a century from 1960. Taking the well-established late-teen peak offending age as given, we find period effects reducing theft in the 1970 s, and period, but particularly cohort effects, reducing crime from the 1990s onwards. We interpret these effects as consistent with variation in the prevailing level of crime opportunities, particularly the ease wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(76 reference statements)
0
3
0
1
Order By: Relevance
“…This is the pattern that would be expected if the security devices made cars difficult but not impossible to steal, where younger, more inexperienced thieves targeted easier-to-take cars that would provide them and their friends with fun (Farrell et al 2011a). A study of US motor vehicle thefts finds, similarly, that the size of subsequent cohorts of offenders was reduced following the introduction of vehicle security improvements (Dixon and Farrell 2020). The debut crime hypothesis is an important correction to the notion that criminality is simply a function of poor parenting, dysfunctional communities, genetic abnormalities, the underclass, or some form of social malaise.…”
Section: Security and Criminalitymentioning
confidence: 92%
“…This is the pattern that would be expected if the security devices made cars difficult but not impossible to steal, where younger, more inexperienced thieves targeted easier-to-take cars that would provide them and their friends with fun (Farrell et al 2011a). A study of US motor vehicle thefts finds, similarly, that the size of subsequent cohorts of offenders was reduced following the introduction of vehicle security improvements (Dixon and Farrell 2020). The debut crime hypothesis is an important correction to the notion that criminality is simply a function of poor parenting, dysfunctional communities, genetic abnormalities, the underclass, or some form of social malaise.…”
Section: Security and Criminalitymentioning
confidence: 92%
“…Saudita (Alotaibi et al, 2017), indican hallazgos en el mismo sentido. Se argumenta que este grupo de población es más propenso a este crimen debido a su capacidad física, estilos de vida y factores ambientales, lo que permite y/o alienta la comisión de este delito (Dixon y Farrell, 2020).…”
Section: Y En Riad Arabiaunclassified
“…Braga and Weisburd (2020) also found support for the hypothesis that Place-based POP strategies reduced crime. Furthermore, a growing body of empirical studies has emerged concerning the role of period and cohort effects in the decline of crime (Dixon and Farrell 2020;Griffiths and Norris 2020;Kim et al 2016;Lu and Luo 2020;O'Brien 2019;O'Brien and Stockard 2009). For example, Kim et al (2016) found that cohort effects rather than period effects seemed to be a more important predictor in the decline of age-specific felony arrest rates in New York State.…”
Section: International Crime Drop In Retrospectmentioning
confidence: 99%